Controlled preparation of multiple mesoporous CoAl-LDHs nanosheets for the high performance of NOx detection at room temperature. Issue 57 (17th September 2020) - Wang, Di; Liu, Zhi; Hong, Ye; Lin, Chong; Pan, Qingjiang; Li, Li; Shi, Keying
Abstract : By fine tuning the metal mole ratio, CoAl-LDHs (CA) with a 2D nanosheet structure were successfully prepared via a one-step hydrothermal method using urea as both precipitator and pore-forming agent. Abstract : By fine tuning the metal mole ratio, CoAl-LDHs (CA) with a 2D nanosheet structure were successfully prepared via a one-step hydrothermal method using urea as both precipitator and pore-forming agent. The morphology of CA samples shows uniform and thin porous hexagonal nanosheets. In particular, CA2-1, prepared with the 2 : 1 molar ratio for Co and Al, respectively, has the highest surface area (54 m 2 g −1 ); its average transverse size of platelets is 2.54 μm with a thickness of around 19.30 nm and inter-plate spacing of about 0.2 μm. The sample exhibits a high sensing performance (response value of 17.09) towards 100 ppm NO x, fast response time (4.27 s) and a low limit of detection (down to 0.01 ppm) at room temperature. Furthermore, CA2-1 shows long -term stability (60 days) and a better selectivity towards NO x at room temperature. The excellent performance of the fabricated sensor is attributed to the special hexagonal structure of the 2D thin nanosheets with abundant mesopores, where the active sites provide fast adsorption and transportation channels, promote oxygen chemisorption, and eventually decrease the diffusion energy barrier for NO x molecules. Furthermore, hydrogen bonds between water molecules and OH − could serve as a bridge, thus providing a channel for rapid electron transfer. This easy synthetic approach and good gas sensing performance allow CoAl-LDHs to be great potential materials in the field of NO x gas sensing.